Multiband guided-mode resonance filter in bilayer asymmetric metallic gratings. (July 2018) - Wang, Yanhui; Li, Xiangjun; Lang, Tingting; Jing, Xufeng; Hong, Zhi
Highlights: A multiband GMR filter in bilayer asymmetric metallic gratings is proposed. The split of the TE or/and TM modes are analyzed in detail. Two to four GMRs based polarization insensitive/sensitive filters are realized. Abstract: In this paper, a guided-mode resonances (GMRs) based multiband filter in bilayer asymmetric metallic gratings is presented. Four sharp dips are generated in the frequency range of 1.4–2.0 THz, which are induced by the split of two GMR modes (TE0 and TM0 ) due to the break of the structure's symmetry. This symmetry of the structure depends on the relative position between the upper layer and lower layer gratings. Therefore, by choosing proper lateral displacement, the split of TE0 or/and TM0 modes can be eliminated. Two-, three-, and four- GMRs based polarization insensitive or sensitive filters are demonstrated numerically.